Organization of distance learning based on the competence modules of a training course - Elena Mikhailovna Petlina (Вестник Майкопского государственного технологического университета, 2023)
In the conditions of the aggravated epidemiological situation, the problem of high-quality training of specialists in the context of distance learning arises. Systematic approach to the formation of standard requirements for the discipline in the context of distance learning makes it advisable to create training modules that allow providing students with knowledge in difficult social conditions and forming key competencies, demonstrating interdisciplinary ties, which is relevant in modern conditions of the educational process. The article discusses the organization of distance learning based on the principle of block-modular technology, taking into account the competence-based approach. The aim of the research is to describe the technology of distance learning based on the competence modules in a training course using an electronic educational environment. The study used the methods of analyzing available sources on the use of distance technologies in educational organizations and generalizing the pedagogical experience of using modern teaching methods. The results of the research consist in analyzing the organization of distance learning based on the creation of competence modules, organizational and pedagogical conditions for the effectiveness of the implementation of a competence-based training module in distance learning. The key conclusions: the technology of organizing distance learning based on the competence blocks, which provides interdisciplinary communication and practice-oriented learning, has been described. The materials of the research can be used as the basis for the development of training courses for the development of educational material and key competencies on the basis of practice-oriented tasks that ensure the successful development of the work program.